2022
DOI: 10.1002/vms3.751
|View full text |Cite
|
Sign up to set email alerts
|

Global molecular epidemiology of microsporidia in pigs and wild boars with emphasis on Enterocytozoon bieneusi: A systematic review and meta‐analysis

Abstract: Background: Microsporidia are spore-forming intracellular pathogens with worldwide prevalence, causing emerging infections in humans and animals. Enterocytozoon bieneusi is a zoonotic species of microsporidia and is responsible for more than 90% of cases of microsporidiosis in humans and animals. Pigs and wild boars are important animal reservoirs of microsporidia. Hence, we aimed to estimate the global prevalence of microsporidia and genetic diversity of E. bieneusi in pigs and wild boars through a set of sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Microsporidia species can cause diarrhea, malabsorption, and possible lung pathology, and host health is a major factor influencing the likelihood of developing these symptoms [46,47]. The most well-known pathogenic species is Enterocytozoon bieneusi, which was not found in this study; however, we found Encephalitozoon romalae, Encephalitozoon enteralis, Encephalitozoon cuniculi, and Encephalitozoon hellem, which can also adversely affect the host [48,49].…”
Section: Discussioncontrasting
confidence: 51%
“…Microsporidia species can cause diarrhea, malabsorption, and possible lung pathology, and host health is a major factor influencing the likelihood of developing these symptoms [46,47]. The most well-known pathogenic species is Enterocytozoon bieneusi, which was not found in this study; however, we found Encephalitozoon romalae, Encephalitozoon enteralis, Encephalitozoon cuniculi, and Encephalitozoon hellem, which can also adversely affect the host [48,49].…”
Section: Discussioncontrasting
confidence: 51%
“…Within microsporidia, there are at least 1,700 recognized species belonging to approximately 220 genera, with 17 species having been found in humans [10]. Molecular epidemiological data have confirmed four major microsporidial species infecting humans, including Enterocytozoon bieneusi, Encephalitozoon cuniculi, Encephalitozoon intestinalis, and Encephalitozoon hellem [32]. Among them, E. bieneusi has been regarded as the most prevalent, accounting for more than 90% of human microsporidiosis cases [32].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular epidemiological data have confirmed four major microsporidial species infecting humans, including Enterocytozoon bieneusi, Encephalitozoon cuniculi, Encephalitozoon intestinalis, and Encephalitozoon hellem [32]. Among them, E. bieneusi has been regarded as the most prevalent, accounting for more than 90% of human microsporidiosis cases [32]. According to the largest metaanalysis of microsporidia globally, the overall prevalence of E. bieneusi infection in humans was 7.9% [28].…”
Section: Introductionmentioning
confidence: 99%